Takhrij and Syarah Hadith of Chemistry: Prohibition of Blowing Hot Drinks and Food - Ima Nurul Imaniah; Tuti Garnasih; Robiah Awaliyah; Asep Supriadin; Maman Lukmanul Hakim (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the prohibition of blowing hot drinks and food. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results and discussion of this research is that if water vapor ( ) reacts with it will form a compound (carbonic acid). The conclusion of this research is takhrij and syarah hadith of the Prophet about the prohibition of blowing hot drinks and food by chemical analysis has the opportunity to reveal the hazards that occur when blowing hot drinks or food.